Analysis of Workload, Fatigue, and Musculoskeletal Complaints among Associate Nurses at Bangli General Hospital - Ni Ketut Guru Prapti; I Wayan Suwirja; Ni Komang Ari Sawitri; Ari Wibawa (Babali Publisher, 2022)
Introduction: Nurses experienced high physical workloads, which may increase the risk of fatigue and musculoskeletal complaints. Nurse’s workplaces, especially hospitals, have not gained serious concern and attention for this issue. Methods: This study was an analytic observational study with a cross sectional design aimed to analyze the workloads, fatigue, and musculoskeletal complaints among associate nurses at Bangli General Hospital, Bali. A total of 46 respondents filled out the research questionnaire given. Results: Based on the NASA-TLX calculations, the associate nurses’ workloads are found to be in the moderate level with the largest indicators on the PD (Physical Demand) and Performance (OP) Scale. By using the Nordic Body Map Questionnaire, most of the respondents had a low risk regarding musculoskeletal complaints and the most of musculoskeletal complaints were felt in the right and left calves, waist and back. The results of the analysis on the 30 items of self-rating test questionnaire found that most nurses experienced fatigue in a low category (57.45%) and only a small percentage of nurses experienced high fatigue category (8.51%). Conclusion: Workloads, fatigue, and musculoskeletal complaints need further investigations to get better understanding of the cause in order to get better solutions.